Resolution of Nonlinear Convection - Diffusion - Reaction Equations of Cauchy Kind by the Laplace SBA Method (European Journal of Pure and Applied Mathematics, 2019)
In this paper, we propose the solution of a few non linear partial di¤erential equa-tions modelling di¤usion, convection and reaction problems Cauchy type. The Laplace SBA method based on combination of Laplaces transform, Adomian Decomposition Method(ADM), Picard prnciple and successive approximations is used for solving these equations.
Keywords: Cauchy kind; di¤ution-convection-reaction problem; Laplace-SBA method.